SISTEM MANAJEMEN KOMUNIKASI DATA JARAK JAUH BERBASIS TEKNOLOGI SMS DAN RADIO TELEMETRY UNTUK PEMANTAUAN KUALITAS AIR - Wahjono, Heru Dwi; Budiman, Bayu (Center for Environmental Technology, 2008)
Nowadays the water quality monitoring project that had been doing by government institution is increase due to decreasing of water quality. Many methods and techniques are developed for water quality monitoring. The communication technology development such as GSM/CDMA technology can be used as new network infrastructure for water quality monitoring. People over the world are now using this technology as new communication medium. With SMS as the one of services from GSM technology people can send or receive messages easily. By using the integration of digital sensor for water quality, digital data logger and GSM modem as communication unit, the water quality can be monitored as cheap as sending the SMS by phone cell. The critical value of water quality parameter also can be monitored and sent to the phone cell of decision maker.Ã‚Â Kata Kunci : Pemantauan Kualitas Air, Teknologi SMS, Radio Telemetry, Early Warning System (EWS), sistem komunikasi GSM (Global System Mobile Communication), SMS (Short Messages Service).